2017
DOI: 10.1039/c6ob02075e
|View full text |Cite
|
Sign up to set email alerts
|

Enediyne-based protein capture agents: demonstration of an enediyne moiety acting as a photoaffinity label

Abstract: Two enediyne based protein-capture compounds 1 and 2 were synthesized. Both these molecules have an aryl sulfonamide for reversible binding with Human Carbonic Anhydrase II (HCA II) and a pyrene moiety for the visualization of a capture event. While compound 1 has an aryl azide as a photo cross-linking agent, compound 2 lacks the azide moiety. Capture experiments with HCA II however show that both 1 and 2 can photo cross-link with the protein as indicated in gel electrophoresis as well as MALDI analysis after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…To clarify the unique role of maleimide moiety in the cyclization of enediynes, two model compounds equipped with the same alkyne functionalities were designed. EDY-A features a benzene group at the ene position, representing common acyclic enediynes, while EDY-B features a maleimide group at the same position. The two tert -butyl groups of different types were installed in the terminal alkyne, tert -butyl tert -butyl­(prop-2-yn-1-yl)­carbamate ( 1 ), as chemical shift indicators for nuclear magnetic resonance (NMR) analysis.…”
Section: Resultsmentioning
confidence: 99%
“…To clarify the unique role of maleimide moiety in the cyclization of enediynes, two model compounds equipped with the same alkyne functionalities were designed. EDY-A features a benzene group at the ene position, representing common acyclic enediynes, while EDY-B features a maleimide group at the same position. The two tert -butyl groups of different types were installed in the terminal alkyne, tert -butyl tert -butyl­(prop-2-yn-1-yl)­carbamate ( 1 ), as chemical shift indicators for nuclear magnetic resonance (NMR) analysis.…”
Section: Resultsmentioning
confidence: 99%
“…All biochemical experiments have been done as described in our previous papers. 18,17 Preparation of GABA-Carboxylic Acid (14). The procedure for preparation of the GABA-carboxylic acid derivative is same as that reported earlier.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The following abbreviations have been used for NMR peak assignments: s = singlet, bs = broad singlet, d = doublet, t = triplet, p = pentet, m = multiplet, and dd = double of doublet. All biochemical experiments have been done as described in our previous papers. , …”
Section: Experimental Sectionmentioning
confidence: 99%
“…The remarkable activity and a striking mode of action made enediyne compounds an attractive target molecules. Motivated by their biological importance, many cyclic and acyclic enediyne derivatives were prepared and their biological activities evaluated. Apart from their role in biologically relevant processes, enediynes are versatile building blocks for the construction of complex aromatic systems through thermal or photochemical activation. Furthermore, rigid, stable, and spatially well-directed enediyne motif can be exploited as an inducer of turn-like conformation. In our previous studies, we showed that enediyne-based small molecule tweezers are efficient Cu­(II) atom binders .…”
Section: Introductionmentioning
confidence: 99%